Study on Tourist Flow Network Structure in Jiangsu Province. Issue 5 (August 2019) - Pu, Rong; Lu, Shuying; Pu, Yuansheng; Tao, Zhuomin; Liu, Peixue
Abstract: In this paper, we used social network analysis (SNA) method to establish and analyse the network structure of the tourist flow of Jiangsu Province in China based on big data, and built a variable model to analyse its influencing factors. The results show that there is an obvious core-edge structure in the network of tourist flow. The centrality index in the southern region of Jiangsu Province is better than that in the northern region. The road distance is the main factor restricting the flow between regions, and the quantity of trains has a significant impact on the tourist flow. That is to say, a place with convenient transportation is the primary choice for people to travel. High quality of tourist facilities and online tourist products can attract tourists. They are also the driving factors for southern Jiangsu Province to play a great role in the tourist flow network.